2008
DOI: 10.1590/s1413-70542008000200041
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade e valor nutritivo da silagem de três cultivares de milheto

Abstract: Com o objetivo de determinar o valor nutritivo da silagem de milheto [Pennisetum glaucum (L.) R. Brown], conduziu-se um experimento, nas dependências do Departamento de Zootecnia da UFLA, utilizando o milheto estabelecido em um Latossolo Vermelho Distroférrico típico textura muito argilosa. Os tratamentos constituíram-se de três cultivares (BRS 1501, BN 1 e Comum) e três idades de corte, 70, 90 e 110 dias, para silagem, semeados em novembro/2003. O delineamento experimental utilizado foi o de blocos ao acaso, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 6 publications
1
8
2
5
Order By: Relevance
“…The NDF content increased linearly with the increasing of nitrogen dosages to the variety ADR 300 and decreased linearly to the hybrid ADR 7010. The values found are lower than those noticed by AMARAL et al (2008) and GUIMARÃES JR. et al (2008) wich studied cultivars of millet, and found values of NDF ranging from 60.15 to 68.63 and 70.50 and 71.2dag kg -1 DM, respectively. The low values of NDF observed in this study may be due to drought stress suffered by the culture, due to low rainfall observed during the experimental period.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…The NDF content increased linearly with the increasing of nitrogen dosages to the variety ADR 300 and decreased linearly to the hybrid ADR 7010. The values found are lower than those noticed by AMARAL et al (2008) and GUIMARÃES JR. et al (2008) wich studied cultivars of millet, and found values of NDF ranging from 60.15 to 68.63 and 70.50 and 71.2dag kg -1 DM, respectively. The low values of NDF observed in this study may be due to drought stress suffered by the culture, due to low rainfall observed during the experimental period.…”
Section: Resultscontrasting
confidence: 75%
“…The pearl millet is grass specie has been widely used by farmers as an alternative to reach the animal requirements in the critical period of the year, due to the fact that it is the forage more resistant to drought and is adapted to low soil fertility, presents fast growth and high yields of phytomass by unit area (AMARAL et al, 2008). It is a culture that shows good development in regions with low rainfall profi le, so, it has been widely used for the production of grass silage during periods of late season and in regions that are characterized by having problems with dry periods or drought (GUIMARÃES JR. et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The CP values obtained in this study were similar to those reported by Amaral et al (2008), between 7.28 and 9.40%. In this research, all silages of the millet genotypes showed enough CP to ensure good ruminal fermentation.…”
Section: Resultssupporting
confidence: 91%
“…The grass allows rotation between grain production and animal production, being a form of agriculture/livestock integration. In this type of management, millets are usually sown after the harvest of the summer crop, known as second crop (Amaral, Evangelista, Salvador, & Pinto, 2008). With the growth of livestock production, millets began to be used as bulk in the form of pasture and silage, which consists of a dual-purpose crop, serving for grain production and mainly forage production, given the high quality of the product compared to other forages (Kollet, Diogo, & Leite, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Torres et al (2008) observaram que, entre sete espécies de cobertura avaliadas, o milheto foi a gramínea com maior produção de fitomassa seca e acúmulo de nitrogênio (N). A produção de forragem do milheto pode variar de 20 a 70 t ha -1 de matéria verde em função da condição de cultivo e época de corte da planta (AMARAL et al, 2008;GUIMARÃES JUNIOR et al, 2009;COSTA et al, 2014).…”
Section: Introductionunclassified